Squamous cell carcinoma of the finger nail bed: an onychomycosis like lesion - Nagaretnam, Vinodharan; Looi, Collin (Universiti Putra Malaysia, 2022)
Squamous cell carcinoma is a form of skin malignancy that involves squamous cells lining the epidermis. It is the second most common form of non-melanoma skin malignancy. We describe a case of squamous cell carcinoma involving the nail bed of an elderly gentleman that was initially diagnosed as a case of fungal infection of the nail bed.